Gymnanthemum coloratum: Review of its Medicinal uses, Phytochemistry and Pharmacological Properties - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2020)
Gymnanthemum coloratum is a shrub or a small tree widely used as traditional medicine throughout its distributional range in tropical Africa. The current study is aimed at reviewing the phytochemistry, pharmacological properties and medicinal uses of G. coloratum. Literature on pharmacological properties, phytochemistry and medicinal uses of G. coloratum was obtained from numerous internet sources such as Scopus, Elsevier, SciFinder, Google Scholar, Pubmed, ScienceDirect, BMC and Web of Science. Other sources of information included pre-electronic sources such as journal articles, theses, book chapters, books and other scientific publications obtained from the university library. The articles published between 1964 and 2020 were used in this study. The current study showed that G. coloratum is used as an anthelmintic, and traditional medicine for reproductive problems, schistosomiasis, liver diseases, sexually transmitted infections, diabetes, sores and wounds, respiratory problems, malaria, skin diseases, fever and gastro-intestinal problems. Ethnopharmacological research identified glaucolides, lactones, amino acids, essential oils, alkaloids, anthocyanins, cardenolids, coumarins, flavonoids, glycosides, leucoanthocyanins, phenols, quinones, reducing sugars, saponins, steroids, tannins, terpenoids and triterpenes from the aerial parts, leaves, roots and stems of G. coloratum. The aerial parts, leaves, roots and whole plant parts of G. coloratum and compounds isolated from the species exhibited anthelmintic, antimicrobial, anti-Blastocystis, anti-inflammatory, anti-sickling, insecticidal and larvicidal, antiplasmodial, antimalarial, antioxidant, antiproliferative, anti-Toxoplasma, hypoglycaemic and antidiabetic and cytotoxicity activities. Gymnanthemum coloratum should be subjected to detailed phytochemical, pharmacological and toxicological evaluations aimed at correlating its medicinal uses with its phytochemistry and pharmacological activities.